Is the Złoczew lignite deposit geologically suitable for the first underground gasification installation in Poland? - Urbański, Paweł; Widera, Marek (Geologos, 2020)
The present study focuses on alternative methods of exploiting lignite in comparison to conventional opencast mining and combustion in power plants for the generation of electricity. In Poland, opencast lignite pits cover large areas, creating social and environmental conflicts. In order to stabilise the production level of electricity and reduce the negative effects of opencast mining, alternative ways of exploiting lignite are suggested, one of these being underground gasification in situ. The Złoczew lignite deposit, which will most likely be exploited in the near future, provides an opportunity to discuss the unconventional method of underground coal gasification (UCG). On the basis of technological and geological criteria that have been established to determine the suitability of Polish lignite for underground gasification, resources to be used this way have been estimated. Through gasification, over 15 million tonnes of lignite can be utilised, which is about 2.5 per cent of resources of the Złoczew deposit intended for opencast mining. With this in mind, we suggest to take action by starting a pilot installation, to be followed by a commercial one for underground gasification after completion of superficial mining. Naturally, any future application of this method will be preceded by assessment of geological conditions at the Złoczew opencast pit.